Effect of Serum Copper on Circulating Angiogenesis-related Factors in Women withPreeclampsia - Najm Nadheer, Khalid; Abdul Aziz abdul Hussein, Afaq; Kadhem Al-Hakeim, Hussein (International Journal of Psychosocial Rehabilitation, 2022)
Preeclampsia (PE) is characterized by a series of clinical features such as hypertension and proteinuria associated with endothelial dysfunction and the impairment of placenta vascular endothelial integrity. This study aimed to investigate the effect of serum copper (Cu) level on some angiogenesis-related factors including vascular endothelial growth factor-A (VEGF-A), soluble Fms-like tyrosine kinase-1 (sVEGF-R1), soluble endoglin (sEng) and ceruloplasmin (CP) in Iraqi women with PE and control pregnant women. Therefore, 60 women with PE in addition to 30 healthy pregnant women were enrolled in the study. Serum concentration of sEng, VEGF-A, sVEGF-R1, and Cu in PE group significantly increased (p